The Manx : the cat with no tail - Quasha, Jennifer (New York : PowerKids Press, 2000)
Relates the history of the Manx cat and describes the physical and other characteristics of this breed which came from the Isle of Man.
Includes index.
Keywords: Manx cat -- Juvenile literature; Manx cat; Cats